Factors Affecting The Performance Of Employees Of The Environmental Service Of South Bengkulu District - Saputra, Doni Susilo; Effendi, Bahman; Adjie, Dwi Nova (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
The analysis method in this study uses Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Determination Coefficient, and hypothesis test using t-test and f-test with the number of samples studied 75 Employees at the South Bengkulu Environmental Service. From the calculation results using SPSS 23 we can see that the work environment, motivation and job satisfaction have a significant effect on employee performance. In this case the significance value of variable X <0.05 is 0.000. The results of the multiple linear regression analysis are the equation Y = 9.895 + 0.250 X1 + 0.379 X2 + 0.165 X3 this illustrates a positive regression direction, meaning that the work environment variables (X1), motivation (X2) and job satisfaction (X3) have a positive effect on employee performance (Y) at the Bengkulu Selatan The magnitude of the determination coefficient value from the calculation results using SPSS can be seen from the determination coefficient value of R square of 0,879. This means that the value of the work environment variables (X1), motivation (X2) and kepuasan kerja (X3) has an effect on the employee performance variable (Y) of 87.9% while the remaining 12.1% is influenced by other variables.